The impact of a DCV-system on the IAQ, energy use, and moisture safety in apartments - a case study. Issue 1 (2nd January 2022) - Abdul Hamid, Akram; Johansson, Dennis; Wahlström, Åsa; Fransson, Victor
Abstract: A novel DCV-system controls the air-change rate for each apartment in multifamily buildings based on two indoor air parameters: 1) the moisture load (supply), and 2) volatile organic compounds . With a central fan, but decentralized control boxes placed outside each apartment, the system controls the air-change rate for each apartment. This paper's main aim is to determine the potential of this DCV-system, through a case study, to: 1) achieve good IAQ, 2) handle the moisture loads appropriately, and 3) achieve good energy efficiency in multifamily buildings. Furthermore, the paper aims to assess the possibility to achieve good IAQ by validating the DCV-system's VOC-controls through measurements of CO2 in apartments. Field measurements show that the system responds appropriately to apartment-specific loads, and that acceptable emission and moisture loads are achieved in most apartments in the case study. The impact that the system has on the energy use was assessed through calculations based on the field measurements. The calculations show that the DCV-system saves energy used for heating the supply-air by 86% in comparison to a mechanically balanced ventilation system without heat recovery, and 22% in comparison to the same system but with heat recovery.